Promoting Consistency in the Deep Seabed: Addressing Regulatory Dimensions in Designing the International Seabed Authority's Exploitation Code. Issue 3 (November 2016) - Markus, Till; Singh, Pradeep
Abstract : On 14 July 2016, the International Seabed Authority (ISA) issued the 'Working Draft Regulations and Standard Contract Terms on Exploitation for Mineral Resources in the Area'. Once finalized, this will form part of the Mining Code, which would govern all aspects of respective deep seabed mining activities. The development of this legal framework does not take place within a legal and conceptual vacuum but in a complex, contested and dynamically developing political and regulatory environment. Numerous rules exist for various mining activities, other uses of the deep seabed and with regard to the conservation of the marine environment. Consequently, the arduous task at hand is to promote consistency between the ISA's developing regime and the existing and emerging international law related to the deep seabed. In this article, we highlight four pertinent issues and two mechanisms which must be addressed and developed in the drafting process of the Exploitation Code to promote consistency. As reliance on the deep seabed increases, promoting consistency is a continuing process in which the ISA would invariably have to participate in and possibly even take charge.